Total Sky Imager observations during POLARSTERN cruise PS122/3 on 2020-05-02 - Ronny Engelmann; Hannes Griesche; Martin Radenz; Julian Hofer; Dietrich Althausen; Andreas Macke; Rico Hengst (PANGAEA, 2023)
The dataset consist of camera shots of the sky. The camera - a total sky imager manufactured by Canon (Powershot) - was mounted at the top of the Research Vessel Polarstern. At the leg 3 (from February until June 2020) of the MOSAIC experiment from Arctic Ocean - Longyearbyen this camera shots were taken with a temporal resolution between 15 minutes and 15 seconds. The dataset represents the visible projection of weather conditions and cloud cover recorded on the vessel Polarstern in the direction near the zenith. These observations are useful for the interpretation of the atmospheric radiation measurements.
In: Engelmann, R et al. (2023): Total Sky Imager observations during POLARSTERN cruise PS122/3, Arctic Ocean - Longyearbyen [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.954218